INTERPRETASI HAKIM PENGADILAN AGAMA MALANG TERHADAP PASAL 55 UU NO. 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH - Yasin, Mohamad Nur; Subkhi, M. Yusuf (Fakultas Syariah, 2012)
This research reveals three causes of authority intersection in section 55 regulation Number 21, year 2008 on sharia banking. First, the transition of Religious Court after regulation Number 33 year 2006 on the changing of regulation Number 7 year 1989 on Religious Court is legalized. Second, there is an image that General Court is more popular than Religious Court. Third, there is socio-political influence and particular interests within the process of formulating the regulation. Judges in Religious Court of Malang are divided into two groups in interpreting section 55 regulation Number 21 year 2008 on Sharia Banking. Firstly, those who apply historical interpretation method argue that the section gives option towards dispute resolution forum. Secondly, those who apply grammatical method stated that section 55 is a historic, because the content has been included in section 49 Regulation Number 3 Year 2006 on the changing of Regulation Number 7 year 1989 on Religious Court which has implication towards the authority reduction of Religious Court on sharia banking. Hasil penelitian menunjukkan kan tiga sebab persinggungan kewenangan dalam pasal 55 UU Nomor 21 Tahun 2008 Tentang Perbankan Syariah. Pertama, adanya masa transisi bagi Peradilan Agama setelah disahkannya UU Nomor 3 Tahun 2006 Tentang Perubahan Atas UU Nomor 7 Tahun 1989 Tentang Peradilan Agama. Kedua, adanya image bahwa Peradilan Umum lebih populer dari Peradilan Agama. Ketiga, adanya pengaruh sosial politik dan berbagai kepentingan dalam proses perumusan UU Nomor 21 Tahun 2008 Tentang Perbankan Syariah. Hakim Pengadilan Agama Malang terbagi dalam dua kelompok dalam menginterpretasikan pasal 55 UU Nomor 21 Tahun 2008 Tentang Perbankan Syariah. Pertama, kelompok yang menggunakan metode interpretasi sejarah berpendapat bahwa pasal 55 muncul untuk memberikan opsi terhadap forum penyelesai sengketa. Kedua, kelompok yang menggunakan metode gramatikal menyatakan, bahwa Pasal 55 UU Nomor 21 Tahun 2008 adalah ahistoris, karena keberadaannya telah ditampung dalam Pasal 49 UU Nomor 3 Tahun 2006 Tentang Perubahan Atas UU Nomor 7 Tahun 1989 Tentang Peradilan Agama yang berimplikasi pada tereduksinya kewenangan Pengadilan Agama di bidang perbankan syariah.